Unintentional deception still deceives - Hardman, Doug (Journal of medical ethics, 2023)
In my recent article, Pretending to care, I argue that a better understanding of non-doxastic attitudes could improve our understanding of deception in clinical practice. In an insightful and well-argued response, Colgrove highlights three problems with my account. For the sake of brevity, in this reply I focus on the first: that my definition of deception is implausible because it does not involve intention. Although I concede that my initial broad definition needs modification, I argue that it should not be modified by involving intention but by involving responsibility.